Human Fatalities from Wild Elephant Attacks: A Fiveyear Autopsy-Based Study - Saptarshi Chatterjee; Ranjan Biswas; Tanmay Sardar; Shobhan Roy (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Human-Elephant Conflict may take many forms, from crop raiding and infrastructuraldamage, to injury or death of humans or elephants. Conflicts or co-existence between human and wildlife ismostly attributed to the loss, degradation, and fragmentation of wildlife habitats through human activitieslike logging, animal husbandry, agricultural expansion, and development projects. The present study isconducted to study the prevalence of fatal wild elephant attacks, the socio-demographic profiles of thevictims along with their nature of injuries and the risk factors associated with these conflicts.Methods: This is a cross-sectional descriptive study, which was conducted by analysing 41 cases of fatalHuman-Elephant Conflicts, which attended to B.S. Medical College Police Mortuary between 2015 to 2019.Conclusion: Authors feel that the blockage of elephant migratory routes, coupled with cultivation ofelephant preferred crops and scarcity of food in the forest in some season, inevitably attracts more humanelephantconflicts.